All in the Stars: the Zodiac in Rabbinic and Contemporary Judaisms - Davis, Stacy (The review of rabbinic Judaism, 2025)
Esther Rabbah 7:11 expands upon Esther 3:7 and B. Megillah 13b, which explain the date assigned for Purim, by having the days of the week, the months of the year, and finally the signs of the zodiac give reasons why Purim cannot happen during their particular times. While the Tanakh frowns upon astrology, that disdain had disappeared by the tenth century CE, as demonstrated by the calendars at Qumran, the writings of Josephus, and the zodiac floors at Beth Alpha and Sepphoris. The transition in Jewish thought from astrology as a non-Jewish symbol of apostasy to a symbol of the faith is exemplified today in the zodiac floor of the Central Reform Congregation (CRC) in St. Louis, MO. The CRC floor visually describes the story in Esther Rabbah while including interreligious and intercultural elements, demonstrating continuity between rabbinic and contemporary Judaisms.